The Effect of Inflation Rate and SBI Interest Rate on Stock Prices in Publicly Listed Telecommunication Companies - Wiwit Hariyanto; Heri Widodo; Endra Wahyu Ningdiyah; Prasetyo Utomo (www.amertainstitute.com, 2025)
The volatility of stock prices in emerging markets is often influenced by macroeconomic indicators such as inflation and interest rates. This study investigates the effect of the inflation rate and the Bank Indonesia Certificate (SBI) interest rate on the stock prices of publicly listed telecommunication companies in Indonesia during the 2020–2023 period. The telecommunication sector was chosen due to its strategic role during the COVID-19 pandemic and its strong contribution to national economic growth. Using a quantitative research design, secondary data were collected from the Indonesia Stock Exchange (IDX) and Bank Indonesia. The sample consisted of 16 telecommunication companies selected through purposive sampling, yielding 64 firm-year observations. Data were analyzed with multiple linear regression supported by descriptive statistics and classical assumption tests, employing SPSS 27 as the analytical tool. The findings reveal that both inflation and SBI interest rates have a significant positive effect on stock prices, with the coefficient of determination (R²) indicating that 90.1% of the variation in stock prices is explained by these macroeconomic factors. This study contributes to the literature by providing empirical evidence of the sensitivity of the telecommunication sector’s stock prices to monetary indicators in the post-pandemic period. The results offer practical insights for investors in making informed investment decisions and for policymakers in formulating monetary policies that indirectly influence capital market performance.